2023
DOI: 10.3389/fbioe.2023.1168408
|View full text |Cite
|
Sign up to set email alerts
|

Nose-to-brain delivery of self-assembled curcumin-lactoferrin nanoparticles: Characterization, neuroprotective effect and in vivo pharmacokinetic study

Abstract: Curcumin (CUR) is a natural polyphenol extract with significant antioxidant and anti-inflammatory effects, which indicates its great potential for neuroprotection. Lactoferrin (LF), a commonly used oral carrier and targeting ligand, has not been reported as a multifunctional nanocarrier for nose-to-brain delivery. This study aims to develop a nose-to-brain delivery system of curcumin-lactoferrin nanoparticles (CUR-LF NPs) and to further evaluate the neuroprotective effects in vitro and brain accumulation in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In addition, Zang et al formulated a curcumin/hydroxypropyl-β-cyclodextrin inclusion complex and reported that the plasma and brain concentrations of the formulation were higher than those in the control group after intranasal administration [ 69 ]. Moreover, Li et al reported that curcumin-lactoferrin nanoparticles demonstrated excellent brain accumulation, prolonged elimination half-life, and improved bioavailability of curcumin after intranasal administration [ 70 ]. Based on this information, it indicates the strong performance of nanoformulations to improve the pharmacokinetics and efficacy of curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Zang et al formulated a curcumin/hydroxypropyl-β-cyclodextrin inclusion complex and reported that the plasma and brain concentrations of the formulation were higher than those in the control group after intranasal administration [ 69 ]. Moreover, Li et al reported that curcumin-lactoferrin nanoparticles demonstrated excellent brain accumulation, prolonged elimination half-life, and improved bioavailability of curcumin after intranasal administration [ 70 ]. Based on this information, it indicates the strong performance of nanoformulations to improve the pharmacokinetics and efficacy of curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the nose-to-brain delivery of nanoscale drugs, selecting appropriate ligands for surface modification of the formulation can increase the affinity between the drug delivery system and the mucosa, leading to enhanced mucosal adsorption. The most commonly used targeting ligands are proteins whose receptors are expressed in the olfactory region, namely lactoferrin ( Li et al, 2023 ) or certain glycoproteins ( Pernet et al, 2023 ). Several lectins, such as wheat germ agglutinin ( Su et al, 2020 ) and solanum tuberosum lectin ( Chen et al, 2012 ), have also been used to promote nose-to-brain drug delivery.…”
Section: Methods To Improve Brain-targeted Nasal Mucosal Drug Deliver...mentioning
confidence: 99%
“…Pure lactoferrin can also, through self-assembly, combine with small molecule drugs to form nanoscale formulations suitable for intranasal administration. Lf and curcumin nanoparticles prepared by desolvation for intranasal administration for AD increased the overall brain accrual to 248.1% with a direct transport efficiency of 59.7% (Li et al, 2023).…”
Section: Nano-drug Carriers Targeting Lactoferrin Receptorsmentioning
confidence: 99%
“…(c) Transferrin-modified nano-polymer negatively used for nose-to-brain schematic diagram (Sonali, Singh, et al, 2016b). (d) Self-assembled curcumin-lactoferrin nanoparticles for the treatment of AD (Li et al, 2023).…”
Section: Nano-drug Carriers Targeting Transferrin Receptorsmentioning
confidence: 99%